From isolation to detection, advancing insights into endothelial matrix-bound vesicles - Sahimy Ayus-Martinez; William Meza-Morales; Jesus Jimenez-Osorio; Maria Buendia-Otero; Luis López; Lisandro Cunci; Donald O. Freytes; Camilo Mora (Extracellular Vesicle)
Matrix-bound vesicles (MBVs), an integral part of the extracellular matrix (ECM), are emerging as pivotal factors in ECM-driven molecular signaling. This study is the first to report the isolation of MBVs from porcine arterial endothelial cell basement membranes (A-MBVs) and thyroid cartilage (C-MBVs), the latter serving as a negative control due to its minimal vascular characteristics. Using Transmission Electron Microscopy (TEM), Nano-Tracking Analysis (NTA), Electrochemical Impedance Spectroscopy (EIS), and Atomic Force Microscopy (AFM), we orthogonally characterized the isolated MBVs. We detected the presence and preservation of vascular endothelial cadherin (CD144) in A-MBVs, its low to non-detetcted in C-MBVs, in which SOX9, a chondrocyte marker, was detected. Moreover, we developed a prototype of an immuno-functionalized screen-printed electrode designed for the immunoadsorption of CD144+ MBVs. This device facilitated the electrochemical detection of the targeted vesicles and allowed for their subsequent topological characterization using AFM, which verified the integrity and morphology of CD144+ MBVs post-immunoadsorption. These advancements enhance our comprehension of MBVs as conveyors of tissue-specific signals and pioneer new avenues for harnessing their cargo in biomedical applications. This research sets a significant precedent for future studies on the application of MBVs in regenerative medicine and ECM signaling.